Bot sangkhro̜ khō̜sanœ̄ botbāt Krasūang Sāthāranasuk nai satawat thī 21 (Sathāban Wičhai Rabop Sāthāranasuk, 2011)
Proceedings of a conference on direction and proposals for the improvement of the roles and work of the Public Health Ministry, Thailand.